Pengaruh Ketidakpastian Pekerjaan dan Keterlibatan Karyawan terhadap Niat Pindah Pekerjaan melalui Dukungan Organisasi yang Dirasakan (POS) sebagai Variabel Perantara di Kalangan Karyawan Outsourcing di PT. XYZ Sidoarjo - Pipit Fadilatul Fitri; Ida Aju Brahma Ratih; Abdul Halik (Journal of Economics, Management, and Accounting, 2025)
The high turnover intention among outsourced employees at PT. XYZ in Sidoarjo highlights the importance of understanding the psychological factors that influence the decision to change jobs. This study analyzes the influence of job insecurity and employee engagement on turnover intention, with perceived organizational support (POS) as a mediating variable. This study contributes theoretically by expanding the understanding of the dual role of POS in unstable employment relationships, and practically by providing implications for the management of outsourced workers in the manufacturing industry. Using an explanatory quantitative approach, data were collected from 189 outsourced employees and analyzed using PLS-SEM. The results show that job insecurity has a positive and significant effect on turnover intention. Employee engagement has a significant effect on POS, but does not directly reduce turnover intention. POS is proven to have a significant effect on turnover intention and mediates the inconsistent relationship between employee engagement and turnover intention. Meanwhile, POS does not mediate the effect of job insecurity on turnover intention. The research model was able to explain 30.5% of the variation in turnover intention, confirming that in the context of outsourcing, organizational support is not yet able to curb turnover intention when job insecurity remains high. Practically, this study recommends strengthening job security, clarifying career prospects, and improving the quality of organizational support relevant to outsourced employees to reduce turnover intention more effectively.